Extraskeletal osteosarcoma: A European Musculoskeletal Oncology Society study on 266 patients. (March 2017) - Longhi, A.; Bielack, S.S.; Grimer, R.; Whelan, J.; Windhager, R.; Leithner, A.; Gronchi, A.; Biau, D.; Jutte, P.; Krieg, A.H.; Klenke, F.M.; Grignani, G.; et al.
Abstract: Purpose: Prognosis of extraskeletal osteosarcoma (ESOS) is reported to be poorer than that of skeletal osteosarcoma. This multicenter retrospective study aimed to evaluate factors influencing ESOS prognosis. Patients and methods: Members of the European Musculoskeletal Oncology Society (EMSOS) submitted institutional data on patients with ESOS. Results: Data from 274 patients treated from 1981 to 2014 were collected from 16 EMSOS centres; 266 patients were eligible. Fifty (18.7%) had metastases at diagnosis. Of 216 patients with localised disease, 211 (98%) underwent surgery (R0 = 70.6%, R1 = 27%). Five-year overall survival (OS) for all 266 patients was 47% (95% CI 40–54%). Five-year OS for metastatic patients was 27% (95% CI 13–41%). In the analysis restricted to the 211 localised patients who achieved complete remission after surgery 5-year OS was 51.4% (95% CI 44–59%) and 5-year disease-free survival (DFS) was 43% (95% CI 35–51%). One hundred twenty-one patients (57.3%) received adjuvant or neoadjuvant chemotherapy and 80 patients (37.9%) received radiotherapy. A favourable trend was seen for osteosarcoma-type chemotherapy versus soft tissue sarcoma-type (doxorubicin ± ifosfamide) regimens. For the 211 patients in complete remission after surgery, patient age, tumour size, margins and chemotherapy were positive prognostic factors for DFS and OS by univariate analysis. At multivariate analysis, patient age (≤40 years versus >40 years) (P = 0.05), tumour size (P = 0.0001) and receipt of chemotherapy (P = 0.006) were statistically significant prognostic factors for survival. Conclusion: Patient age and tumour size are factors influencing ESOS prognosis. Higher survival was observed in patients who received perioperative chemotherapy with a trend in favour of multiagent osteosarcoma-type regimen which included doxorubicin, ifosfamide and cisplatin. Highlights: Extraskeletal osteosarcoma benefit of adjuvant chemotherapy. Osteosarcoma-type chemotherapy seems to be more effective than soft tissue sarcoma chemotherapy. The role of adjuvant radiotherapy is not sure.